1970
DOI: 10.1002/bjs.1800571009
|View full text |Cite
|
Sign up to set email alerts
|

Tape-closed and sutured wounds: A comparison by tensiometry and scanning electron microscopy

Abstract: SUMMARYI . The ability of a wound to resist rupture (energy absorption or 'toughness') is calculated from its tensile strength and extension ('give '). This property of the wound is only half that of normal tissue after 5 months of healing.2. A biomechanical study shows that tape-closed wounds develop greater tensile strength than sutured wounds. However, they are more brittle and have, as a result, no greater ability to resist rupture. Other considerations such as obliteration of dead space, prevention of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…12 Wounds closed with adhesive strips have been shown to have equal or superior tensile strength compared with sutured wounds 10 days after wound closure. 23 In a comparison of 7 adhesive strips, Steri Strip Skin Closures showed the best adhesion time when an artificial force was applied. 24 The theoretical disadvantages of adhesive tapes are that they frequently fall off, have lower tensile strength than sutures, have the highest rate of dehiscence, require the use of toxic adjuncts, cannot get wet, and cannot be used in areas of hair.…”
Section: Discussionmentioning
confidence: 98%
“…12 Wounds closed with adhesive strips have been shown to have equal or superior tensile strength compared with sutured wounds 10 days after wound closure. 23 In a comparison of 7 adhesive strips, Steri Strip Skin Closures showed the best adhesion time when an artificial force was applied. 24 The theoretical disadvantages of adhesive tapes are that they frequently fall off, have lower tensile strength than sutures, have the highest rate of dehiscence, require the use of toxic adjuncts, cannot get wet, and cannot be used in areas of hair.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, this technique allows for faster restoration of tensile strength equal or superior at 10 days than with sutured wounds. [20] Skin tension is equal throughout the length of the incision and this method avoids post-operative “railroad track” scarring from sutures. [17] Microporous strips allow the passage of gas and water from the skin surface, which make the environment unsuitable for bacterial proliferation and therefore lead to less wound infections.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for the closure of wounds by tapes instead of sutures has been reviewed by Golden et al6 The studies of Ordman and Gillman7 and Forrester et al 8 give an experimental and theoretical basis for expecting improvements after a change to this method of skin closure. Forrester et al8 in their study of collagen in skin wounds showed that taped wounds had greater tensile strength than sutured wounds and that this difference was still appreciable at 150 days.…”
Section: Discussionmentioning
confidence: 99%